A solution synthetic route toward Bi2Se3 layered nanostructures with tunable thickness via weakening precursor reactivity. Issue 9 (21st June 2013) - Wei, Tiaoxing; Zhang, Yun; Dong, Wenjing; Huang, Chanyan; Sun, Yan; Chen, Xin; Dai, Ning
<x xml:space="preserve">Abstract</x> We developed a solution synthetic route to Bi2Se3 layered nanostructures through weakening the reactivity of precursors in a hot‐injection process. Oleylamine (OYA) and its content in precursor solutions determined reliable synthesis and tunable thickness of Bi2Se3 layered nanostructures. The Raman shift of the out‐of‐plane vibration mode (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3g3v7jrk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />A1g1</alternatives>) suggested that the minimum thickness of Bi2Se3 layered nanostructures could be down to ∼3 nm [about three quintuple layers (QLs)] by varying the content of OYA. Both energy dispersive spectroscopy and X‐ray photoelectronic spectroscopy proved that there were no inorganic impurities imported into Bi2Se3 nanostructures. This synthetic approach would bring about more opportunities for flexible preparation of promising layered nanomaterials with tunable thickness for thermoelectric conversion, electrochemical hydrogen storage, and even topological insulators.